Longterm (52-week) Results of a Phase III Randomized, Controlled Trial of Apremilast in Patients with Psoriatic Arthritis - Kavanaugh, Arthur; Mease, Philip J.; Gomez-Reino, Juan J.; Adebajo, Adewale O.; Wollenhaupt, Juergen; Gladman, Dafna D.; Hochfeld, Marla; Teng, Lichen L.; Schett, Georg; Lespessailles, Eric; Hall, Stephen (Journal of Rheumatology, 2015)
To evaluate the efficacy and safety of apremilast, an oral phosphodiesterase 4 inhibitor, over 52 weeks in patients with active psoriatic arthritis (PsA) despite prior treatment.Patients were randomized to placebo (n = 168), apremilast 20 mg BID (n = 168), or apremilast 30 mg BID (n = 168). Patients whose swollen and tender joint counts had not improved by >= 20% at Week 16 were considered nonresponders and were required to be re-randomized (1:1) to apremilast 20 mg BID or 30 mg BID if they were initially randomized to placebo, or continued their initial treatment of apremilast dose. At Week 24, all remaining patients treated with placebo were re-randomized to apremilast 20 mg BID or 30 mg BID.An American College of Rheumatology 20 (ACR20) response at Week 16 was attained by significantly more patients receiving apremilast 20 mg BID (30.4%, p = 0.0166) or 30 mg BID (38.1%, p = 0.0001) than placebo (19.0%). Among patients receiving apremilast continuously for 52 weeks (n = 254), ACR20 response at Week 52 was observed in 63.0% (75/119, 20 mg BID) and 54.6% (71/130, 30 mg BID) of patients. Response was also maintained across secondary outcomes, including measures of PsA signs and symptoms, skin psoriasis severity, and physical function. The nature, incidence, and severity of adverse events were comparable over the 24-week and 52-week periods. The most common adverse events, diarrhea and nausea, generally occurred early and were self-limited.Continuous apremilast treatment resulted in sustained improvements in PsA for up to 52 weeks. Apremilast had an acceptable safety profile and was generally well tolerated.NCT01172938.
EVALuna2:13087